Antimethanogenic effects of soybean straw and seaweed (Sargassum johnstonii) based total mixed ration in crossbred cows - Katwal, Sarishti; Pandya, P R; Trivedi, M M; Sorathiya, K K; Shah, S V (Indian Journal of Dairy Science, 2021)
Ruminants are responsible for 50 % of anthropogenic methane production. Methane has higher global warming potential which is 28 times more than CO2. The present investigation was conducted to evaluate effect of supplementation of soybean straw and seaweed (Sargassum johnstoni) in the ration of dairy cows on methane mitigation and production performance of animals. Six crossbred lactating cows received three treatments in Switch Over Design for 135 days in 3 periods of 45 days each. The treatments consist of T1: TMR with compound concentrate mixture and wheat straw (60:40); T2: TMR with 20 % each of wheat straw and soyabean straw and 60 % compound concentrate mixture and T3: TMR (60:40) with seaweed (Sargassum johnstonii). Methane emission was estimated by SF6 tracer technique. The DM and nutrient intake were at par in T1 and T2 but was significantly low in T3. The milk yield observed was also less in T3 than T1 and T2 which were at par. The methane production significantly reduced by 20.79 % and 16.53% (P